(3CSGS GdHdGZIs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3CMeO Hf eMeO GdcQO s)
(3ChdgG (B:s
(3NjQ efWhb CeGe cd cdGe , hCaVd eUOQ Hg cd cJGH , MeO Gddg hEdi gPG GdUhGH PgH YHO Gddg GdabjQ GdReMTQi ai JUfja cJGH CSGS GdHdGZI hef NUGFU gPG GdcJGH JNjQ eG hbY ai YHGQGJ GdeHOYjf s
(3BNQgG (B:s
(3hef GdeLGR (B: (3PcQ ai CjGe GdYQH ai hbGFYgG (B( (3hPcQge HCjGe Gddg (B) : (3HOeGOeg Ydi GdcaQI eY GdgGA hbjd GdSjd hGdaMd GdgGFL ced GdCSGS s
(3HgG fXGe GdJYbjHIs
(3JGeI ai fUajfs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs